Alterações da hemodinâmica placentária em grávidas com diabetes mellitus tipo I - Maria Marta Teixeira Gomes de Araújo Cunha (2021)
Pregnancies complicated by type I diabetes mellitus are associated with an increased risk of congenital malformations, fetal growth abnormalities, hypertensive disorders and fetal death. Placental vascular malperfusion may cause these complications and their severity can be conditioned by the time elapsed since the diagnosis, the metabolic control and the presence of maternal vasculopathy. With this review, we intend to evaluate how the placental hemodynamics is altered in pregnancies complicated by type I diabetes mellitus.